2018
DOI: 10.2196/10456
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Contingency Management Intervention to Improve Pre-Exposure Prophylaxis Adherence: Pilot Trial

Abstract: BackgroundPre-exposure prophylaxis (PrEP) provides a strong preventative benefit to individuals at risk for HIV. While PrEP adherence is highly correlated with its efficacy, adherence rates are variable both across and within persons.ObjectiveThe objective of this study was to develop and pilot-test a smartphone-based intervention, known as mSMART, that targets PrEP adherence. mSMART provides contingency management in the form of monetary incentives for daily PrEP adherence based on a real-time adherence asses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 48 publications
(45 reference statements)
0
58
0
1
Order By: Relevance
“…There are studies in adolescent HIV prevention research with preliminary data suggesting the feasibility and acceptability of apps in supporting PrEP adherence, however, trial results on efficacy are pending [51‐54]. The “Raincoat” app used in this trial did not show efficacy in PrEP adherence or service retention.…”
Section: Discussionmentioning
confidence: 85%
“…There are studies in adolescent HIV prevention research with preliminary data suggesting the feasibility and acceptability of apps in supporting PrEP adherence, however, trial results on efficacy are pending [51‐54]. The “Raincoat” app used in this trial did not show efficacy in PrEP adherence or service retention.…”
Section: Discussionmentioning
confidence: 85%
“…Technology-based interventions were reported in five studies and they can be viewed as uniting the micro- and mesosystem levels . These technologies were considered to be useful for service users and providers for setting reminders, [ 92 , 103 , 106 , 112 , 130 ] monitoring and surveillance (particularly those with a high risk of contracting HIV), [ 52 , 91 , 112 ] education and information, [ 82 , 102 , 106 , 130 ] tailoring care, [ 102 ] providing counselling, [ 52 , 66 , 77 , 107 , 131 ] adherence, [ 53 , 67 , 73 , 79 , 89 , 91 93 , 103 , 106 , 111 , 112 , 131 , 132 ] recording dosing regimen (event-based, intermittent or daily), [ 93 , 106 , 112 , 132 ] allowing individuals to feel connected and even providing maps that show where PrEP is offered in the local area [ 106 , 133 ]. In their studies, Refugio et al [ 130 ], Stekler et al [ 107 ] and Fuchs et al [ 89 ] implemented a text-based support strategy, which allowed participants to send messages, set reminders, download and receive information, abate stigma and enable staff to provide additional support throughout the PrEP user’s journey.…”
Section: Resultsmentioning
confidence: 99%
“…Tellalian et al [63] and Stekler et al [107] identified that service level support was needed in order to improve correct use of PrEP, adherence and retention. Other barriers to PrEP adherence at service user level included medication concerns, for example the pill being too big or tasting unpleasant, [108] missing clinics, [109] forgetting to take medication [54,75,103,110] and cost [111,112]. Disruption in routine was also reported [54,93,103,108] but Vaccher et al [103] stated that this could be reduced by carrying spare medication for emergencies.…”
Section: Theme Three: Prep Adherence Within Formal Service Structuresmentioning
confidence: 99%
“…Intervention trials are underway to test simple mobile technology products (e.g., text messaging services, mobile applications) to support PrEP adherence [25][26][27]. In addition, there are ongoing investigations of alternative dosing strategies (e.g., intermittent dosing) that may be more acceptable and manageable for persons unable to adhere to daily dosing [28,29]. A long-acting injectable version of PrEP (Cabotegravir) is also awaiting approval by the US Food and Drug Administration and may prove useful for individuals who experience difficulty taking a daily medication [32].…”
Section: Plos Onementioning
confidence: 99%